Augmented reality mobile app-based multimedia learning of pencak silat to enhance the junior high school students’ learning outcomes - Nur Rohmah Muktiani; Soegiyanto Soegiyanto; Siswantoyo Siswantoyo; Hedi Ardiyanto Hermawan; Setya Rahayu (Jurnal Cakrawala Pendidikan, 2022)
The present study aims to produce Augmented Reality Mobile App-based multimedia of Pencak silat learning for junior high school students. APPED Research and Development model was applied by following several stages, including Analysis and Initial Research, Design, Production, Evaluation, and Dissemination. The data were collected using questionnaire and tests. The product was evaluated in three stages, namely one to one, small group, and field (effectivity test) evaluation. Three material experts were involved in rating the product validation with a mean of 4.77 (very good). Meanwhile, mean score from three Media Experts was 4.80 (very good). The mean score of product evaluation for one-to-one evaluation was at 4.62 (very good), the small group at 4.80 (very good), and the field at 4.56 (very good). A significant improvement was detected from the mean score of the learning outcomes from pretest to posttest (p=0.0000.05). Therefore, it can be concluded that Augmented Reality Mobile App-based multimedia of Pencak silat learning was effective to improve JHS students’ achievement and was able to be used in the Pencak silat learning for JHS students.